2008
DOI: 10.1590/s0104-11692008000200011
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors in patients with type 2 diabetes mellitus

Abstract: This study was carried out to evaluate the risk factors of type 2 diabetic patients through sociodemographic data, habits of health, anthropometric and biochemist profiles, assisted at a basic public health care unit in Maringá, Paraná. Sixty-six patients, 56 women aged over than 50 years-old were interviewed. High prevalence factors for cardiovascular risk were observed, such as: overweight and obesity, hypertension, dyslipidemia, sedentariness and inadequate diet. Data suggested the need for multidisciplinar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 12 publications
3
7
0
7
Order By: Relevance
“…The results from this study highlight that, among diabetic individuals, hypertension is twice more frequent when compared to the population in general. This agrees with Carolino et al (15) who showed in their study that about 67% of diabetic patients were classified as hypersensitive.…”
Section: Mean Global Risk Score Among Different Sex In Each Groupsupporting
confidence: 92%
“…The results from this study highlight that, among diabetic individuals, hypertension is twice more frequent when compared to the population in general. This agrees with Carolino et al (15) who showed in their study that about 67% of diabetic patients were classified as hypersensitive.…”
Section: Mean Global Risk Score Among Different Sex In Each Groupsupporting
confidence: 92%
“…Carolino et al 11 study reported, there was only one patient older than 80 years, while the age range with the highest concentration of individuals was from 60 to 69 years old (51.51%), followed by 50 to 59 years (30.30%) and 70 to 79 years (16.67%). These findings are coherent with those found in other studies carried out with samples originating from health services.…”
Section: Discussionmentioning
confidence: 93%
“…As options, strategies coming from clinical management and based on risk stratification and biopsychosocial factors of the population, such as operative groups and supported self-care, can be decisive in the gaining of self-efficacy by PHC users and, consequently, in the achievement of lower hospitalization rates 28 . The implementation of multidisciplinary intervention programs at basic health units can promote the adoption of health practices among people with diabetes, as pointed by a study conducted in a municipality in northwestern Paraná 29 . In general terms, PHC must be associated with the improvement in decision-making as to drug prescriptions, to additional exam requests and to other assessments, including improvement in glycemic control, decrease in consultations with specialists and in search for emergency services 30 .…”
Section: Discussionmentioning
confidence: 99%